A Maya Universe in Stone - Houston, Stephen D.; Houston, Stephen D. (Book collections on Project MUSE., 2021)
"The first study devoted to a single sculptor in ancient America, as understood through four unprovenanced masterworks traced to a small sector of Guatemala"--